Designing for dealing with drone dilemmas : ten trade-offs in unmanned aircraft systems' human systems integration - Woltjer, Rogier ; 0000-0001-8549-6516; Prem Maben, Rohith ; 0009-0008-9411-0695; Woodlock, John; Tyllström, Rikard; van Zyl, Christo (Human systems integration in the design of complex transport systems : a practical guide, 2026)
This chapter discusses trade-offs that need to be struck while developing Unmanned Aircraft Systems (UAS) operations. Ten trade-offs are outlined, pertaining to technical systems, to human operators, and to the combined sociotechnical system in its operational and organizational environment, which have implications for Human-Systems Integration (HSI) in multiple phases of the systems engineering life cycle. These ten trade-offs include a wide range of variables and aspects such as aircraft design aspects and materials, mission performance, energy use, payload capacity, hardware and software, fault tolerance and robustness, adaptive capacity, interactivity, automation, distribution of control, time horizons of control and mission goals, adversarial aspects, and the envisioning of operations. The trade-offs are exemplified from our UAS-lab operational experience and the scientific literature. Rather than listing trade-offs exhaustively, the aim is to encourage developers, designers, and other analysts of complex UAS operations (but also other safety-critical transportation) to explicitly consider trade-offs and trade spaces specific to their own development activities, as a conceptual and reflective tool, critical to effective Human-Systems Integration.